Global research trends on forest rehabilitation and biodiversity: A bibliometric analysis - Nurlaily Lavianti; Jati Batoro; Fitri Candra Wardana; Muhammad Lubab; Muhammad Fathur Rouf Hasan; Maisuna Kundariati; Rochman Hidayat (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Forest ecosystems play a crucial role in maintaining biodiversity, regulating climate systems, and supporting human well-being. However, widespread deforestation, land-use change, and climate change have caused severe forest degradation worldwide, making forest rehabilitation and biodiversity a global environmental priority. Although the scientific literature linking forest rehabilitation and biodiversity has grown rapidly, a comprehensive understanding of research trends, major contributors, and thematic evolution remains limited. This study presents a global bibliometric analysis of scientific publications on forest rehabilitation and biodiversity from 2000 to 2026 using data retrieved from the Scopus database. A total of 562 peer-reviewed articles were analyzed using the Bibliometrix package in R and the Biblioshiny interface to examine publication trends, authorship patterns, international collaboration networks, influential journals and articles, and thematic structures. The results revealed a steady increase in publication output, with significant acceleration after 2015, coinciding with growing global attention to forest rehabilitation and environmental sustainability issues. Research in this field is highly collaborative, with strong contributions from developed countries, particularly the United States, the United Kingdom, and China. Thematic analysis showed that reforestation, biodiversity, and conservation are the most central and well-developed themes, while climate change, ecosystem services, and land-use dynamics represent emerging areas receiving increasing attention. Overall, this study provides a comprehensive overview of the scientific landscape of research on forest restoration and biodiversity while identifying knowledge gaps and future research directions. These findings offer valuable insights for researchers, policymakers, and practitioners in developing evidence-based strategies for ecological restoration and biodiversity conservation.